Variables associated with run out opportunities in cricket: coaches' perceptions versus video analyses of the Indian Premier League 2018/2019 seasons - Sholto-Douglas, Robert (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
The purpose of this investigation was to add a scientific element to the understanding of run out opportunities in T20 (twenty/twenty) formats, which would in turn, provide recommendations to players and coaches around the topic of run outs. Due to a lack of research in this field, the study was two-fold, as there is little research known on this topic. Firstly, surveying experienced coaches on what they would expect to take place during run out opportunities from different areas of the field in a T20 game. Secondly, the study looked at what happened during successful and unsuccessful run outs from different areas of the field in two Indian Premier League (IPL) seasons. The aim of the study was to determine what variables, within an area of fielding, led to a successful or non-successful run out from different zones in the field. Coaches were required to fill out a survey which asked them to give their expectations on run out opportunities during a T20 competition. The data from the questionnaire would be used to gain a greater understanding of the way coaches understand different characteristics of run outs and whether this matched the findings of the second part of this study. The second part of the study investigated run out opportunities in two consecutive IPL seasons, based on video footage, looking at how different variables impacted successful or marginally missed run out opportunities in different areas of the field and at different times of the game. The areas were put into four different zones. Zone 1 being close to the batter, zone 2 being in the inner ring, zone 3 being on the edge of the ring and zone 4 being boundary fielders. Most of the coaches believed that in zone 1 of the field, the bowler would have the most opportunities, where in fact, based on the video footage, these fell to the wicket-keeper. In zone 2 there were a larger range of fielding positions (10) that run outs fell to when analysing video footage. The coaches supported this by often naming the same fielding positions. There was a divide in zone 3. Most run out opportunities from the video footage came to extra cover, where most coaches didn't believe that would be the case and rather mentioned mid-off and mid-on. When analysing video footage in zone 4, it had two fielding positions (long on and deep mid-wicket) make up the majority of run out chances in this area and these two positions were quoted by most of the coaches as having the most run out opportunities fall to them. Throughout the findings, as concluded from the video footage, there were some results that matched the coaches' expectation and some results where findings from the video footage differed from the coaches' expectations. These findings are all useful. Firstly, it validates coaching practices. Secondly, it provides coaches with greater insight as to where they aren't getting it correct in their fielding training. In conclusion, this study found that although coaches perceptions, for the most part, matched what took place on the field, there were instances where we saw the opposite action take place. This has important practical implications for coaching and practice.
Keywords: Indian Premier League; Cricket -- Coaching; Video analysis; Fielding; Run out